Political Justice in a Republic : James Fenimore Cooper's America. - McWilliams, John P.; McWilliams, John P., Jr. (Berkeley : University of California Press, 2021)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1972.
Intro -- Acknowledgments -- Contents -- A Chronology of James Fenimore Cooper -- Introduction: Law and the Neutral Ground -- 1. The American Revolution: Problems of Patriotism -- 2. First Notions of America -- 3. The American Democrat in Europe -- 4. The Conservative Democrat in Templeton -- 5. Moral Law in the Wilderness: The Indian Romances -- 6. The Gentry and Legal Change -- 7. Fanciful Kingdoms: The End of the Republic -- 8. Way of the Reactionary -- Appendix A -- Appendix B -- Works Cited -- Index of Subjects and Cooper's Ideas -- Index of Cooper's Works -- Index of Names
Description based upon print version of record.
JSTOR
Keywords: Cooper, James Fenimore, -- 1789-1851 -- Political and social views; Cooper, James Fenimore, -- 1789-1851; Politics and literature -- United States -- History -- 19th century; Political fiction, American -- History and criticism; National characteristics, American, in literature; Politique et littérature -- États-Unis -- Histoire -- 19e siècle.; Politique-fiction américaine -- Histoire et critique; National characteristics, American, in literature; Political and social views; Political fiction, American; Politics and literature; United States; 1800-1899; Cooper, James Fenimore -- 1789-1851 -- Political and social views; Cooper, James Fenimore -- Political and social views; National characteristics, American, in literature; Political fiction, American -- History and criticism; Politics and literature -- United States -- History -- 19th century; Criticism, interpretation, etc; History